The relationship between achievement in pure mathematics and educational achievement, and cultural abut students of the College of Basic Education at the University of Mustansiriya. (Journal of the College of Basic Education, 2022)
The main objective of this study is to reveal the potential relationship between achievement in pure mathematics (computers, topology, nodal analysis, linear programming), educational achievement (specialized teaching methods, management and supervision, curriculum and book analysis), and cultural (Arabic), The sample of the students of the College of Basic Education at the University of Mustansiriya - Department of Mathematics, has reached (110) students from the fourth stage students, the study tried to answer the following key question:- What is the possible relationship between achievement in mathematics, and achievement in educational and cultural materials I have a sample of students from the College of Basic endodontic at the University of Mustansiriya? After testing the hypothesis and the resulting sub-hypotheses and in an attempt to answer the question the following results were reached:- There is a relationship between the average scores of the College of Basic Education at the University of Mustansiriya - Department of Mathematics in mathematics and the average achievement in educational and cultural subjects, although it is a weak link, as the weakness of this link is the nature of the tendency of each member of the study towards learning mathematics.- The results of the study sample show that students with a tendency to learn mathematics led to their higher achievement in mathematics and a decrease in their achievement in educational and cultural subjects and vice versa.- The results concluded that the tendency towards learning mathematics and high level of achievement is related to the level of achievement in educational and cultural subjects, although it is a weak link. This weak link is due to the weak desire to study literary versus scientific subjects.